Akad dan Kesesuaian Fitur Wakaf Produk Asuransi Jiwa Syariah - Alam, Azhar; Hidayati, Sukri (EQUILIBRIUM, 2020)
This study describes the appropriateness of AlliSya Protection Plus Unit Link waqf features based on the DSN-MUI Fatwa regarding Endowment of Insurance Benefits and Investment Benefits of Sharia Life Insurance at PT Asuransi Allianz Life Indonesia. This study aims to study the contracts contained in the waqf product features with uses field research studies, literature reviews and qualitative data analysis. The results of this study indicate that the implementation of Waqf Unit AlliSya Protection Plus features is following the National Sharia Board Fatwa because it has fulfilled the provisions for waqf of insurance benefits, waqf of investment benefits, and provisions of ujrah. This waqf feature product utilizes tabarru, wakalah bil ujrah, mudaraba, waqf, wills, and qardh contract. Waqf funds will be distributed to waqf institutions (nazir) received by the policyholder dies. The implementation of waqf features in sharia life insurance products is encouragement in increasing the collection of endowment funds, thereby increasing both the welfare of society and economic development.